(3JaUjd GdfTCJjf aj JMUjd GdSYGOJjfs - (3GdMSjf Hf eMeO Hf GdeaVd, CHh GdbGSe GdCUagGfj (B((3Ch GdCUHgGfj(B) (3GdeYQha HGdQGZH,J (B502 (3g` s
(3ChdgG (B:s
(3GdMeO ddg bGd CHh GdbGSe GdMSjf Hf eMeO Hf GdeaVd GdQGZH gPg QSGdI ai JaUjd GdfTCJjf GdePchQg ai bhdg JYGdi (B:" (3hdbO YdeJe GdfTCI GdChdi adhdG JPcQhf (B" s
(3BNQgG (B:s
(3aMjfFP ef MUd dg gPg GdefRdI CaVd ef cKjQ ef GdedGFcI CYGffG Gddg JYGdi HdhZ gPg GdefRdI bGd CHh GdbGSe GdMSf Hf eMeO Hf GdeaVd GdQGZH JQGLe CHhGH gPG GdcJGH EKfi hKdGKjf HGHkG hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3QJHI GdeDda Ydi KdGKI hKdGKjf HGHkG haUd ajgG GdfTCI GdChdi hGdfTCI GdCNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B59s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(4818) s
Keywords: (3GdeLGejYs